1989
DOI: 10.3382/ps.0680399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phospholipids on the Conformation of Chicken High Density Lipoprotein

Abstract: Apolipoprotein A-I (apo-A-I), the major protein component of chicken high density lipoprotein (HDL), was isolated by hydrophobic interaction chromatography from the lipoprotein fraction of plasma. The apo-A-I was identified from its amino acid composition and molecular weight (by electrophoresis). The isolated protein contained 15% lipid, in the form of neutral lipids and free fatty acids, as compared with 50% lipid, including phospholipid, in intact HDL. The conformation of the isolated protein, as determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…ApoA1 is also found on the surface of mammalian HDL in addition to ApoE. Although previous studies have indicated that ApoA1 is expressed in a variety of tissues in the chicken, including hepatocytes, intestinal cells, adipocytes and myocytes (Blue et al, 1982;Shackelford and Lebherz, 1983;Rajavashisth et al, 1987;Brown, 1989), this is the first report showing ApoA1 expression in macrophages. Intriguingly, as ApoA1 is the only apolipoprotein required for HDL formation in chickens, the possibility that chicken macrophages have the unique ability to produce HDL precursors in order to mediate lipid efflux cannot be ruled out.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…ApoA1 is also found on the surface of mammalian HDL in addition to ApoE. Although previous studies have indicated that ApoA1 is expressed in a variety of tissues in the chicken, including hepatocytes, intestinal cells, adipocytes and myocytes (Blue et al, 1982;Shackelford and Lebherz, 1983;Rajavashisth et al, 1987;Brown, 1989), this is the first report showing ApoA1 expression in macrophages. Intriguingly, as ApoA1 is the only apolipoprotein required for HDL formation in chickens, the possibility that chicken macrophages have the unique ability to produce HDL precursors in order to mediate lipid efflux cannot be ruled out.…”
Section: Discussionmentioning
confidence: 75%
“…Birds transport large quantities of yolk during several periods of their life history: in ovo and during the early post-hatching period, during the active egg-laying cycle when eggs are being formed, and during follicular atresia (Shackelford and Lebherz, 1983;Rajavashisth et al, 1987;Brown, 1989;Barron et al, 1999). During follicular atresia, large yolk-filled follicles involute and yolk lipid is extruded into the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%